2022
DOI: 10.31703/gmcr.2022(vii-i).01
|View full text |Cite
|
Sign up to set email alerts
|

Impact of English Language on Career Opportunities in the Private Sector of Pakistan: A Case Study of Jazz Digital House Multan

Abstract: The present study investigated the impact of English language on career opportunities of employees of Jazz Digital House Multan Pakistan,working in various domains. A quantitative approach was applied to obtain the employees' perceptions as an individual’s perspective. Data were collected through a four-point Likert scale questionnaire from 111 Jazz employees. A survey form was circulated through Google form, and the respondents’ responses were collected online. Descriptive and inferential statistics were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
1
0
2
Order By: Relevance
“…Penguasaan bahasa Inggris yang merupakan bahasa Global dinilai menjadi faktor penting untuk mendapatkan peluang kerja dan juga meningkatkan peluang pengembangan karir (Roshid, 2013). Dari beberapa penelitian diketahui bahwa penguasaan bahasa Inggris di negara yang bahasa utamanya bukan bahasa Inggris memberikan peluang besar bagi seseorang untuk mendapatkan peluang kerja dan memiliki karir yang lebih baik (Shrestha, et al, 2017;Ting et al, 2017;Ali et al, 2020).…”
Section: Hasilunclassified
See 1 more Smart Citation
“…Penguasaan bahasa Inggris yang merupakan bahasa Global dinilai menjadi faktor penting untuk mendapatkan peluang kerja dan juga meningkatkan peluang pengembangan karir (Roshid, 2013). Dari beberapa penelitian diketahui bahwa penguasaan bahasa Inggris di negara yang bahasa utamanya bukan bahasa Inggris memberikan peluang besar bagi seseorang untuk mendapatkan peluang kerja dan memiliki karir yang lebih baik (Shrestha, et al, 2017;Ting et al, 2017;Ali et al, 2020).…”
Section: Hasilunclassified
“…Sebaliknya ketidakmahiran dalam berbahasa Inggris bisa menjadi penyebab seseorang tidak bisa mempertahankan pekerjaannya. Keterampilan bahasa Inggris merupakan syarat wajib untuk menemukan pekerjaan yang sesuai (Ali, Nawaz, & Imran, 2020).…”
Section: Gambar 1 Persebaran Jenis Kelamin Responden Penelitianunclassified
“…Research on the importance of English language skills in the workplace for immigrants has shown that language pro ciency, particularly in English, is positively associated with immigrants' earnings (Bleakley & Chin, 2004). Ali et al revealed that English language skills increase individuals' chances of career success, break barriers to nding good jobs, and have a very signi cant impact on career-boosting opportunities (Ali, Nawaz, & Imran, 2022). Immigrants' ability to speak in English opens doors to many opportunities, whereas "inability to speak English prevents them from advancing to better-paying jobs" (Cope, 2021).…”
Section: Introductionmentioning
confidence: 99%